Jim Dinsmore letter to Thomas Kent regarding birds sighted by himself and others, November 19, 1980 - Dinsmore, James J.et al (1980)
Jim Dinsmore letter to Thomas Kent. Jim Dinsmore provides a summary of birds, locations and dates that he and others have sighted, and includes a citation for a bibliography he mentioned. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed